The Awareness Survey of Clinical Trials Among Medical Students of South Rajasthan, India - K Malav, Puja; Jhalani, Gopal; Yadav, Harsh; Dhaked, Sunita; Bhatt, Ravi (Scripta Medica, 2022)
Background / Aim: Clinical trials are becoming more popular in India, but its awareness among the medical professionals remains far from satisfactory. Clinical research/trial can help medical students in developing the critical thinking abilities necessary for medical practice. In this era of evidence-based medicine, the integration of medical education and clinical research is crucial to ensure that scientific findings are translated into clinical practice. The present study aimed to find out the awareness about clinical trial among undergraduates. Methods: After obtaining approval from the Institutional Ethics Committee, this cross-sectional study was conducted on students from first to final year and interns after taking their consent. A sample of 390 respondents was analysed. A structured questionnaire was used to measure the objective of this study. The proportion of successfully answered questions in each group was computed and the results were sorted into pre-determined grades as follows: As excellent - 80-100 %, moderate - 50-80 % and terrible – less than 50 %. Results: Out of 390 undergraduate students, for the statement regarding the concept of clinical trials, around 28.2 % fell in the good category, 57.7 % in the average category and 14.1 % in the poor category. Regarding the statement about role of the United States Food and Drug Administration (US FDA) in approving new drug, 34.1 % were poor responders, 52.6 % were average and 13.3 % were good. The statements regarding the participation in the clinical research study showed that majority were in the poor and average response category (45.6 % and 41.5 %, respectively) as compared to only 12.8 % in the good category. Conclusions: The overall awareness of clinical trials was low among students, the medical undergraduates are future innovators, clinicians and scientific explorers. It would be better if they are trained at earlier days of learning about clinical trials/research and medical ethics. These can be made a part of medical curriculum so that they can build their concrete future.